Collision analysis of top tensioned riser - Cao Quoc Dung (2011)
In the offshore platform, the riser is an integral part to assist the drilling, production and transportation of the oil. Due to the increasing demand in the oil and gas industry, the exploration and production process have to go into deeper water. The deeper the water is, the more the oil risers are prone to collision. The main motivation of this final year project report is to present explicit results and analysis on the impact of two top tensioned risers under collision. A response surface of critical stress developed in the impacted risers will be established as a function of collision velocity and impact angle between the two. The effects of tension force in the riser as well as acceleration of riser prior to impact on the clashing damage will also be investigated.